Pengaruh faktor keuangan dan non keuangan terhadap tindakan penghindaran pajak - Ihsan Saddam Ahmadi; Arief Rahman (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2020)
This study aims to analyze the influence of financial factors represented by leverage and non financial factors represented by political connections, firm size, the audite committee, corporate social responsibility (CSR) on tax avoidance behavior. The sampel used in this study were 61 manufactured companies that listed ini Indonesia Stock Exchange in the year of 2015-2017. The method used in sampling process is purposive sampling. This study used descriptive statistic, classic assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and multiple linera regression with SPSS. While testing the hypothesis using the t test (partial regression coefficient test) and the coefficient of determination test (Adjusted R2). The results of this study indicates that audite commite and leverage partially significant effect on Avoidance of Tax. While political connections, firm size, and corporate social responsibility (CSR) has no effect on tax avoidance.